METHODS AND MEANS OF IMPROVING THE SECURITY OF ELECTRONIC DOCUMENT EXCHANGE SYSTEMS BASED ON NEURAL NETWORKS - Muminova , Sunbula (Innovative Development in Educational Activities, 2023)
In the age of rapid technological advancement, electronic document exchange systems have become an integral part of various sectors, ranging from finance and healthcare to government and education. However, the increased reliance on digital platforms has also escalated security concerns. Cyber threats, including data breaches and identity theft, pose significant challenges to the integrity and confidentiality of electronic document exchange systems. To combat these challenges, researchers and developers have turned to innovative solutions, incorporating neural networks to enhance the security of these systems. This article explores the methods and means of improving the security of electronic document exchange systems, focusing on advancements made through neural networks-based approaches.